Proceedings of 2017 Chinese Intelligent Automation Conference (Lecture Notes in Electrical Engineering,, 2018)
The proceedings present selected research papers from the CIAC'17, held in Tianjin, China. The topics include adaptive control, fuzzy control, neural network based control, knowledge based control, hybrid intelligent control, learning control, evolutionary mechanism based control, multi-sensor integration, failure diagnosis, reconfigurable control, and etc. Engineers and researchers from academia, industry, and government can gain valuable insights into solutions combining ideas from multiple disciplines in the field of intelligent automation.